Key factors to prioritize when preparing for the Olympic Games - Nassis, G. P.; Millet, G. P. (Journal of Sport and Health Science, 2024)
We need more research that will fulfill the needs of athletes and coaches. This is a common statement, highly relevant nowadays only a few weeks before the commencement of the Paris 2024 Olympic Games. To fill this gap, we have identified 6 topics that we feel coaches and athletes would be interested in learning more to optimize their preparation for the Olympics. These topics are Athletes` readiness for competition Preparation for competition and tapering Altitude/hypoxic training Coping with heat during the Olympic Games New technologies and new equipment Preparation for team sports